Mapping body-related research within the experimental landscape of anorexia nervosa: a scoping review - Gentili, Sofia; Meregalli, Valentina; Risso, Gaia; Giovannini, Serena; Zambon, Eugenia; Bassolino, Michela; Serino, Andrea; Favaro, Angela; Collantoni, Enrico (Frontiers in Neuroscience, 2025)
IntroductionAnorexia Nervosa (AN) is a complex psychiatric disorder characterized not only by restrictive eating behaviors and fear of weight gain, but also by emotional dysregulation, cognitive rigidity, and a profound disturbance in bodily experience. While bodily disturbance is clinically central, its multifaceted and pre-reflective nature has made it difficult to investigate experimentally. This scoping review aims to map the experimental case-control literature on AN from the past 15 years, with particular attention to how studies on body representation are represented within the broader field of AN research, both in terms of their prevalence and their subdivision into specific thematic domains.MethodsA systematic search was conducted on PubMed, Scopus, and Web of Science. Studies were included if they involved an experimental task comparing individuals with AN to healthy controls.ResultsThe search yielded six hundred and three eligible studies, each classified into one or more thematic domains: cognition, emotion/social cognition, food-related processing, reward, and body representation. Among these, one hundred and sixty four studies addressed body representation and were further categorized into five subdomains: body image, perception of other bodies, body schema, sensory processing, and interoception.DiscussionWhile studies on cognition, emotion, reward, and food processing often used standardized paradigms and showed moderate methodological consistency, research on the bodily domain was notably heterogeneous. This reflects both the conceptual complexity of corporeality and the lack of unified frameworks for its empirical investigation. A recent shift toward multisensory and embodiment-based paradigms suggests increasing interest in implicit and integrative models of body representation. By identifying patterns, gaps, and emerging trends, this review underscores the need for greater conceptual clarity and interdisciplinary convergence. Advancing the experimental study of body representation in AN may support more comprehensive models of the disorder and enhance our understanding of bodily experience in psychiatric conditions.